TUDUHAN SELINGKUH : SANKSI DAN PEMBUKTIAN DALAM BINGKAI ADAT - Sulistio, Dody; Lestari, Dewi (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
This paper aims to find out the Legal Sanctions d for Perpetrators of Infidelity Allegations and their evidentiary mechanisms according to the Customary Law of Lubuk Ruso Village, Pemayung District, Batang Hari Jambi Regency. This research uses Descriptive Qualitative research with data collection methods carried out by observation, interviews and documentation. Based on the research that has been carried out, the following results and conclusions are obtained: Allegations of infidelity according to customary law are proven by the presence of witnesses and oaths in the trial. Customary institutions in enforcing the law on perpetrators of allegations of infidelity (slander) are based on the eight-year-old regulations in the dago-dagi article, namely all forms of acts that violate the common/public interest, causing domestic chaos. Such as mistakes against the government, making slander (provocations) and creating domestic chaos. The punishment was a full, double-folded wake, namely a buffalo, 800 bushels of rice, 800 coconuts, 8 sacks of white cloth and a bag of semanih. Meanwhile, according to the traditional head in the form of buffalo, rice, coconut, semanic selemak, asam segamo, eaten by many people. These sanctions/fines are first discussed by the customary apparatus, then the sanctions/fines imposed are in accordance with the results of the rembukan carried out by the customary apparatus. If the perpetrator cannot pay the sanction, then his heirs can help pay it, if no one can pay the claim then it can be sued in court